FACTORS THAT DETERMINE BUYING INTERESTS OF FOREIGN TOURISTS IN CHOOSING ACCOMMODATIONS IN TEGALLALANG VILLAGE, GIANYAR , BALI - Sari, Ni Putu Ratna; Sri, Anak Agung Putri (Institut Pariwisata dan Bisnis Internasional, 2020)
A number of accommodations are available in Tegallalang Village, because of its location that is close to central Ubud. Along with the increase in foreign tourist arrivals, then this study aims to analyze the factors that determine the interest of foreign tourists in the selection of accommodation in the village of Tegallalang, Gianyar Bali. This study used 50 respondents with accidental sampling technique. Data will be analyzed by factor analysis. The results showed characteristics of tourists who stay at accommodation in Tegallalang Village were dominant Australian citizenship 18%, Length of their stay is 3-7 days (72%), based on age in 26-30 years old (36%). Characteristics based on occupation dominant as employed (48%) and purpose of visit for leisure (58%). Tourists choose villa for 68% as a place to stay, this is because the villa is more privacy than others. The factors that influence the buying interest of foreign tourists in choosing accommodation are the first is the factor of room quality, the second is the location factor, the third is the price factor and the fourth is accommodation security factor. The dominant factor that determines it is the room quality factorThe next research that will be conducted in the future is guest satisfaction toward accommodation in Tegallalang Village is highly expected.